Mythopoetic and Social Problematics of Fantasy in the Works of Lucius Shepard - Adilova , Shakhnoza Rakhimovna (The Lingua Spectrum, 2026)
The article examines the mythopoetic and social problematics of fantasy in the works of Lucius Shepard. Its aim is to demonstrate how the fantastic in Shepard’s prose exceeds an escapist function and becomes a mode of thinking about power, memory, colonial violence, and peripheral experience. The material includes the novel Life During Wartime, selected texts from The Jaguar Hunter and The Ends of the Earth, and the Griaule cycle collected in The Dragon Griaule. The study combines historical-literary, mythopoetic, narratological, and contextual methods. The analysis shows that the figure of Griaule organizes not only plot but also space, economy, art, and collective imagination. The social dimension emerges through the interaction of fantasy, magical realism, horror, and science fiction, which loads genre form with concrete historical anxiety. The article concludes that Shepard renovates late twentieth- and early twenty-first-century American fantasy through hybrid poetics and an unusually sharp social sensibility.